Diagnostics of Times of Increased Probabilities of Strong Earthquakes in The Himalayan Seismic Belt Using Pattern Recognition Algorithm CN - Bhatia, S. C.; Chalam, S. V.; Gaur, V. C.; Levshina, T. A.; Vorobieva, I. A.; Subedi, L. N. (Tribhuvan University Journal, 2010)
Not available. Key words: Strong Earthquakes; Himalayan Seismic Belt; Algorithm CN Tribhuvan University Journal Volume XVI, 1993 Page: 1-11 Uploaded date: 3 October, 2010